Mutant and non-mutant neoantigen-based cancer vaccines: recent advances and future promises - Mohamad Omar Ashi; Fathia Mami-Chouaib; Stéphanie Corgnac (Open Exploration Publishing Inc., 2022)
Major advances in cancer treatment have emerged with the introduction of immunotherapies using blocking antibodies that target T-cell inhibitory receptors, such as programmed death-1 (PD-1) and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), known as immune checkpoints. However, most cancer patients do not respond to immune checkpoint blockade (ICB) therapies, suggesting the development of resistance mechanisms associated with either an insufficient number of preexisting tumor-specific T-cell precursors and/or inappropriate T-cell reactivation. To broaden clinical benefit, anti-PD-1/PD-1 ligand (PD-L1) neutralizing antibodies have been combined with therapeutic cancer vaccines based on non-mutant and/or mutant tumor antigens, to stimulate and expand tumor-specific T lymphocytes. Although these combination treatments achieve the expected goal in some patients, relapse linked to alterations in antigen presentation machinery (APM) of cancer cells often occurs leading to tumor escape from CD8 T-cell immunity. Remarkably, an alternative antigenic peptide repertoire, referred to as T-cell epitopes associated with impaired peptide processing (TEIPP), arises on these malignant cells with altered APM. TEIPP are derived from ubiquitous non-mutant self-proteins and represent a unique resource to target immune-edited tumors that have acquired resistance to cytotoxic T lymphocytes (CTLs) related to defects in transporter associated with antigen processing (TAP) and possibly also to ICB. The present review discusses tumor-associated antigens (TAAs) and mutant neoantigens and their use as targets in peptide- and RNA-based therapeutic cancer vaccines. Finally, this paper highlights TEIPP as a promising immunogenic non-mutant neoantigen candidates for active cancer immunotherapy and combination with TAA and mutant neoantigens. Combining these polyepitope cancer vaccines with ICB would broaden T-cell specificity and reinvigorate exhausted antitumor CTL, resulting in the eradication of all types of neoplastic cells, including immune-escaped subtypes.